An Assessment on the Safety Management Towards Implementation of Construction Projects Throughout the National Irrigation Administration – Upper Pampanga River Integrated Irrigation Systems (NIA-UPRIIS) - Geronimo, Joseph Paolo A; Cordova, Angelica B; Loria Jr., Salvador A; Cortez, Kyle Eduard G (International Journal of Progressive Research in Science and Engineering, 2023)
This study investigated the safety management practices in the implementation of construction projects at the National Irrigation Administration – Upper Pampanga River Integrated Irrigation Systems (NIA – UPRIIS). The study employed a quantitative approach, utilizing a questionnaire survey to gather data from 35 project-in-charges from different NIA – UPRIIS division offices. The findings revealed that the majority of project-in-charges possess adequate knowledge of construction safety and health protocols. However, there were some areas where safety practices could be improved, such as consistent enforcement of personal protective equipment (PPE) use and conducting thorough risk assessments at every stage of the project. Based on the findings, the study recommends conducting thorough risk assessments, developing comprehensive safety plans, investing in safety training programs, implementing regular on-site inspections, encouraging incident reporting, and establishing effective communication channels to enhance safety performance in NIA – UPRIIS construction projects.